The Crime Factors of Premeditated Murder Committed by Children Against Children - Yogi Aranda (Faculty of Law, Universitas Lampung, 2020)
The crime of premeditated murder by minors against their own peers is a very cruel thing. The formulation of the problem in this study is what is the cause and how to deal with the crime of premeditated murder with child offenders and victims. The method used in solving the problem of this research is to use a Normative Juridical and Empirical Juridical approach. Based on the results of research and discussion, it is analyzed (1) Factors that cause the crime of premeditated murder with child offenders and victims, namely: Low levels of education and spiritual values, a hostile environment (Family, School and Society), Rapid technological development , Low economic ability. (2) Efforts in overcoming the crime of premeditated murder with child offenders and victims are preventive measures: conducting raids in the form of sharp weapons, checking identity in nightclubs, conducting legal counseling to schools and legal counseling in the form of interactive dialogue through electronic radio media and efforts Repressive: focuses on the judicial process in accordance with the provisions contained in Act Number 11 of 2012 concerning the Criminal Justice System for Children. The suggestion in this research is that it is expected that the Judges in deciding the case of a child who committed a murder crime does not merely use the means of punishment. Judges must prioritize child protection and must be more prudent in seeing the involvement of children, whether children are perpetrators or participating, so that judges are expected to provide facilities beyond the punishment of children who commit murder crimes, it is better for law enforcers to carry out law enforcement against children who commit premeditated murder must be mutually coordinate and prioritize children's rights. Law enforcement officials must provide comfort to children who commit crime, in order to improve the personality of children in the future, to further optimize counseling and dissemination by regional and municipal officials to schools and villages in order to increase the knowledge of citizens related to the impact of the community. commit a crime.